Mesenchymal Stromal Cells, CFU-F, From Bone Marrow of untreated Advanced Breast and Lung Cancer Patients Suppress Fibroblast Colonies Formation From Healthy Marrow - Hofer, Erica Leonor (2010)
We have shown that bone marrow (BM) from untreated advanced lung and breast cancer patients (LCP and BCP) have a reduced number of colony-forming unit fibroblasts (CFU-Fs) or mesenchymal stem cells (MSCs). Factors that regulate the proliferation and differentiation of CFU-F are produced by the patients' BM microenvironment. We have now examined whether conditioned media (CM) from patients' CFU-F-derived stromal cells also inhibits the colony-forming efficiency (CFE) of CFU-F in primary cultures from healthy volunteers (HV)-BM. Thus the number and proliferation potential of HV-CFU-F were also found to be decreased and similar to colony numbers and colony size of patients' CFU-F. Stromal cells from both of these types of colonies appeared relatively larger and lacked the characteristic spindle morphology typically seen in healthy stromal cells. We developed an arbitrary mesenchymal stromal cell maturational index by taking three measures consisting of stromal cell surface area, longitudinal and horizontal axis. All stromal indices derived from HV-CFU-F grown in patients' CM were similar to those from stromal elements derived from patients' CFU-F. These indices were markedly higher than stromal indices typical of HV-CFU-F cultured in healthy CM or standard medium [alpha-medium plus 20% heat-inactivated fetal bovine serum (FBS)]. Patients' CM had increased concentrations of the CFU-F inhibitor, GM-CSF, and low levels of bFGF and Dkk-1, strong promoters of self-renewal of MSCs, compared to the levels quantified in CM from HV-CFU-F. Moreover, the majority of patients' MSCs were unresponsive in standard medium and healthy CM to give CFU-F, indicating that the majority of mesenchymal stromal cells from patients' CFU-F are locked in maturational arrest. These results show that alterations of GM-CSF, bFGF, and Dkk-1 are associated with deficient cloning and maturation arrest of CFU-F. Defective autocrine and paracrine mechanisms may be involved in the BM microenvironments of LCP and BCP.